2020
DOI: 10.3390/ma13184038
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure Characteristics of Foam Composite with Active Carbon

Abstract: Characterization of porous materials is essential for predicting and modeling their adsorption performance, strength, and durability. However, studies on the optimization of the pore structure to efficiently remove pollutants in the atmosphere by physical adsorption of construction materials have been insufficient. This study investigated the pore structure characteristics of foam composites. Porous foam composites were fabricated using foam composite with high porosity, open pores, and palm shell active carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It was shown that microporous and mesoporous biomaterials have very good or good absorption ability, due to high specific surface area and high pore volume. In turn, macroporous samples possess relatively poor swelling ability [ 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that microporous and mesoporous biomaterials have very good or good absorption ability, due to high specific surface area and high pore volume. In turn, macroporous samples possess relatively poor swelling ability [ 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, nitrogen desorption experiments were carried out at the saturated temperature of liquid nitrogen. The multi-point Brunauer–Emmett–Teller (mBET) theory was used to calculate the surface area, and the average pore diameter was calculated using the Barrett–Joyner–Halenda (BJH) model [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Its interior contains a large number of uniform and small pores [10][11][12][13][14], so it is also known as foaming cement. It is a new type of waste benefit, environmental protection, energy saving material [15], but the current application is relatively limited, mostly used in housing insulation and heat insulation [16], sound insulation [17], fire retardant [18], shock prevention and shock absorption [19], pollution absorption [20] and other fields, in the field of desertification control, is basically still in the laboratory stage. Different from thermal insulation, sound insulation and other fields of foaming cement materials need very low water absorption rate [21] (generally require water absorption rate in more than ten percent or even several percent), applied to desertification treatment of foam cement materials require higher water absorption rate [22], generally required in more than 30 %, so that it may be widely used in desertification areas with very little precipitation and sediment water content.…”
Section: Introductionmentioning
confidence: 99%